Challenges in English Writing Skills from the Perspective of Hospitality Students at SMKN 1 Singaraja - Kadek Dharma Jaya Wardana; Ni Wayan Surya Mahayanti; Ni Luh Putu Era Adnyayanti (EDU SOCIETY: JURNAL PENDIDIKAN, ILMU SOSIAL DAN PENGABDIAN KEPADA MASYARAKAT, 2025)
In the globalization era, writing skills in English become an important ability for vocational students, especially in the hospitality field which demands professional communication in writing. This study highlights the challenges that hospitality students at SMKN 1 Singaraja face in English writing skills, an area that needs to be explored from the perspective of vocational students. This study aims to find out the challenges in writing skills in English from the perspective of hospitality students at SMKN 1 Singaraja. This research uses descriptive qualitative method, where the author distributes questionnaires and describes it in written form. To support the data, the researcher also conducted interviews with students to find out more about the difficulties experienced. The subjects of this study were 15 students of 10th grade hospitality students at SMKN 1 Singaraja. The results showed that: (1) students have difficulty in writing skills especially in the vocabulary aspect, (2) students lose motivation in writing English, and (3) students have difficulty in using tenses. The implications of the findings suggest the need for more adaptive and contextualized learning approaches, including vocabulary enrichment and simple but applicable grammar learning. This research provides a practical contribution for educators to develop teaching materials that are more suited to the needs of hospitality students, to improve writing competencies that are essential in the hospitality industry.